Campus Students Teach as Agents of Social Change: An Analysis of the Sociology of Education on the Adaptation of Teacher and Student Technology - Reski P; Tahir Kasnawi; Hasbi (proceedings.icesy, 2026)
The development of digital technology requires schools to adapt to an increasingly technology-based way of working and learning. However, in practice, not all teachers and students have the same readiness to utilize technology effectively. The Teaching Campus Program is one of the efforts to bridge this gap through the direct involvement of students at school. This research aims to describe the role of Teaching Campus students in supporting the adaptation of teacher and student technology in the assignment school. The research was conducted with a qualitative approach through document analysis which included activity reports, teaching journals, and program documentation. The results of the study show that students play an active role in helping teachers and students adapt to technology through the development of interactive learning media, the application of digital-based teaching journals, and the creation of school profile videos. Mentoring that is carried out collaboratively and gradually encourages increased teachers’ confidence in using technology and increases student involvement in the learning process. However, the sustainability of technology practices still depends on the support of the school and the commitment of teachers after the student’s assignment period ends. These findings show that Teaching Campus students function as an initial trigger for change, not as the only actor in the digital transformation of education.